Liver Fibrosis Progression in HIV–HCV-Coinfected Patients Treated with Distinct Antiretroviral Drugs and Impact of Pegylated Interferon/Ribavirin Therapy. Issue 3 (April 2014) - Fernández-Montero, José V; Barreiro, Pablo; Vispo, Eugenia; Labarga, Pablo; Sánchez-Parra, Clara; de Mendoza, Carmen; Treviño, Ana; Soriano, Vicente
Background: Advanced liver fibrosis frequently develops in patients with chronic hepatitis C coinfected with HIV. Non-invasive techniques for staging liver fibrosis, such as transient elastometry, may allow both periodic monitoring and examination of large patient populations. Methods: A programme of liver fibrosis assessment using transient elastometry has been ongoing at our institution since 2004. All HIV-HCV-coinfected patients having ≥2 examinations separated by >18 months were included. Liver fibrosis progression (LFP) was defined as an increase in liver stiffness from <9.5 kPa (Metavir F0-F2) to >9.5 kPa (Metavir F3-F4), or an increase >30% in patients with baseline Metavir F3-F4. Results: A total of 545 HIV-HCV-coinfected patients were analysed (mean age 41 years, 71% male, 81% intravenous drug users, mean body mass index 23.3 kg/m 2, 4.2% hepatitis B surface antigen-positive, 8.4% alcohol abuse, mean CD4 + T-cell count 519 cells/μl). At baseline, 527 patients were on antiretroviral therapy, with the most frequent third drug being atazanavir (19.7%), efavirenz (15.9%), lopinavir (13.1%) or nevirapine (7.2%). A total of 99 (18%) patients experienced LFP during a mean (sd ) follow-up of 70.9 (15.7) months. Use of protease inhibitors (OR 4.93, 95% CI 1.73, 14.0; P =0.03) and male gender (OR 5.12, 95% CI 1.37, 19.1; P =0.01) were associated with LFP. By contrast, the achievement of HCV clearance following pegylated interferon/ribavirin (PEG-IFN/RBV) therapy (OR 0.27, 95% CI 0.1, 0.79; P =0.02) was protective. Lopinavir exposure was significantly associated with LFP (OR 1.02, 95% CI 1.0, 1.04; P =0.03), whereas nevirapine was protective (OR 0.94, 95% CI 0.9, 0.99; P =0.02). Conclusions: The use of protease inhibitors, mainly lopinavir, is associated with increased LFP in HIV–HCV-coinfected patients. By contrast, nevirapine therapy and, particularly, HCV clearance with PEG-IFN/RBV significantly reduce LFP.